Autonomy of the system of higher education in the conditions of integration of Ukraine into the European educational area - Olena Rayevnyeva (Problems and Perspectives in Management, 2018)
In the conditions of Ukraine’s integration into the European educational area, it is vital to follow the trend of democratization of the society and obtaining freedoms in various spheres of the Ukraine’s development. Therefore, the concept of university autonomy is one of the key in development of the Ukrainian higher education system, whereas obtaining additional freedoms in management of the higher educational institutionsenhances its competitiveness. The concept of autonomy has a dual nature, thereby impacting the need to determine such a level of autonomy that would ensure high quality of higher education in the frame of the country’s national development. The article analyzes methodological approaches to calculation of autonomy of the higher education system in Ukraine. As a result, the methods of the European University, which include examination of autonomy by four components: organizational, staff, financial and academic, are chosen for the research. The development level method and the cluster analysis are selected as mathematical tools. Following the development level method, an integral indicator for each component of autonomy is obtained. On the basis of calculation, it is determined that Ukraine has a low level of autonomy across all the components. Through the use of the cluster analysis, 5 clusters of autonomy of the higher education system are built, whereupon they obtain their economic interpretation. Analysis of the Ukrainian higher education system’s place in the European educational area shows that the system of the Ukrainian higher education is categorized within the cluster with a low level of autonomy.